Ensino de língua inglesa e letramento crítico em tempos neoliberais: autoetnografia de um professor em formação - Lopes, Fabrício Cavalcante (2020)
This dissertation aims to analyze and reflect on my education as an English language teacher by participating as a collaborator of the team that offered an education course for English language teachers in the state of Alagoas. The study, placed in indisciplinary Applied Linguistics‘ field (MOITA LOPES, 2008), is organized into three sections. In the first section, I present the theories that guided this work. They are: the concept of critical literacy (JANKS, 2012, MCLAUGHLIN; DEVOOGD, 2004), the concept of neoliberalism (BROWN, 2015, 2016), a discussion on teacher education (NÓVOA, 1995; 1997), and the use of additional language (SANTOS, 2012, MOREIRA JUNIOR, 2016). In section two, I describe the research methodology of an autoethnographic nature (ADAMS, ELLIS, BOCHNER, 2015). The choice for autoethnography made it possible to reflect on myself, causing a continuous exercise of self-analysis and increased my responsibility in my decision-making and in my actions, inside and outside the classroom. In section three, I present the interpretation of the data, which is divided into five parts: 1) Enchantment blinds, in which I discuss my attempts to direct the conversations with the teachers of the education course to the interests of my research; 2) in another brick in the wall, I interpret the harmful effects of neoliberal rationality in education; 3) in local fruits, I interpret the reconstruction of meanings that I have been going through, whether in terms of teaching the English language, teacher training, or the meanings attributed to the public school; 4) in (re) visiting to (re) build, I describe the feeling and perceptions of returning to attend an educational environment to which I have already been subjected and 5) in (re) building meanings, I interpret my perception about the effects of the education course in a participating teacher, in his students and in myself. In the final remarks, I ponder on the effects of neoliberalism on education, on possible ways of subversion to this rationality and I appreciate the gains that the investigation has provided me.